2021
DOI: 10.1159/000519811
|View full text |Cite
|
Sign up to set email alerts
|

The Kynurenine Pathway in Acute Kidney Injury and Chronic Kidney Disease

Abstract: <b><i>Background:</i></b> The kynurenine pathway (KP) is the major catabolic pathway for tryptophan degradation. The KP plays an important role as the sole de novo nicotinamide adenine dinucleotide (NAD<sup>+</sup>) biosynthetic pathway in normal human physiology and functions as a counter-regulatory mechanism to mitigate immune responses during inflammation. Although the KP has been implicated in a variety of disorders including Huntington’s disease, seizures, cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 201 publications
2
25
0
1
Order By: Relevance
“…33 The complex enzyme systems in the kidney could be involved in the kynurenine pathway, and the kidney injury can affect metabolic enzyme activities, which has a direct impact on metabolic disorder. 34 There are some literature reports that chronic nephrosis is often accompanied by the disorder of tryptophan metabolism, and the results of our research show that, compared with the control group, the tryptophan levels in the PBZ-exposed rats showed a significant decrease. 34 4,6-Dihydroxyquinoline is a downstream product of the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 57%
“…33 The complex enzyme systems in the kidney could be involved in the kynurenine pathway, and the kidney injury can affect metabolic enzyme activities, which has a direct impact on metabolic disorder. 34 There are some literature reports that chronic nephrosis is often accompanied by the disorder of tryptophan metabolism, and the results of our research show that, compared with the control group, the tryptophan levels in the PBZ-exposed rats showed a significant decrease. 34 4,6-Dihydroxyquinoline is a downstream product of the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 57%
“…During pathological inflammatory states, flux through the KP is increased due to the upregulation of the first pathway enzyme (indolamine 2,3-dioxygenase) across multiple organs ( 45 48 ). Evidence points to a potential role for the KP in noncardiac surgery-associated AKI ( 49 ). Observational studies in adults with AKI from a mix of etiologies have identified increased circulating kynurenic acid and kynurenine/tryptophan ratios in subjects with AKI ( 50 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of exogenous kynurenic acid decreases ischemia-reperfusion-induced AKI in mice ( 58 ), and blockade of the KP at kynurenine 3-monooxygenase with shunting toward kynurenic acid has a similar effect ( 29 ). These findings suggest that kynurenic acid may be protective in isolated ischemia-reperfusion injury, likely through a combination of antioxidant, anti-inflammatory, and N -methyl- d -aspartate receptor antagonist properties ( 49 ). Reduction of downstream oxidant, proapoptotic, N -methyl- d -aspartate receptor agonist KP metabolites may also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The TRP-KYN pathway is activated in AKI, showing usually an increase in its metabolites [ 17 , 18 ]. Upregulation of the TRP-KYN pathway in AKI can be explained by the higher concentrations of IFN-γ and other pro-inflammatory cytokines following IR injury, which in turn activate the TRP-KYN pathway via its rate-limiting enzyme IDO [ 19 ]. In our study a strong linear correlation of change in the kynurenine/tryptophan ratio with change in cystatin C and beta-2-microglobulin was seen in the RIPC group.…”
Section: Discussionmentioning
confidence: 99%